2022
DOI: 10.3389/fmicb.2022.964823
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial-resistant characterization of Bacillus cereus isolated from ready-to-eat rice products in Eastern China

Abstract: Bacillus cereus is a major food-borne bacterial pathogen in the world, which can cause diarrhea and emetic syndrome. This study aimed to reveal the quantitative prevalence of B. cereus in ready-to-eat (RTE) rice products in Eastern China and to gain essential information on the characteristics of B. cereus isolates. A total of 91 out of the 1071 samples were positive for B. cereus. The contamination level of B. cereus in 0.5 % of RTE rice product samples outnumbered 103 CFU/g. The number of B. cereus attained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…A study from Sri Lanka showed a 56% detection rate of Bacillus cereus in 200 samples of Chinese-style fried rice [ 34 ]. Another study in Zhejiang Province showed that the detection rate of Bacillus cereus in boiled rice reached 71.4% [ 35 ]. Leftover food contaminated with Bacillus cereus , if not properly preserved before consumption, can lead to reproduction and toxin production, which can ultimately lead to foodborne diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Sri Lanka showed a 56% detection rate of Bacillus cereus in 200 samples of Chinese-style fried rice [ 34 ]. Another study in Zhejiang Province showed that the detection rate of Bacillus cereus in boiled rice reached 71.4% [ 35 ]. Leftover food contaminated with Bacillus cereus , if not properly preserved before consumption, can lead to reproduction and toxin production, which can ultimately lead to foodborne diseases.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR (500 MHz, DMSO) δ 8.28 (d, J = 2.3 Hz, 1H), 8.24 (d, J = 9.0 Hz, 1H), 8.04 (dd, J = 9.0, 2.3 Hz, 1H). 13 (6-Bromoquinoxaline-2,3-diyl)bis(phosphonic acid) (10). Compound 10 was synthesized according to general procedure D, using tetraethyl (6-bromoquinoxaline-2,3-diyl)bis(phosphonate) 10c (80 mg, 0.16 mmol), bromotrimethylsilane (209 μL, 1.6 mmol), and DCM (15 mL).…”
Section: 3-dichloro-6-(4-chlorophenyl)quinoxaline (15c)mentioning
confidence: 99%
“…histolyticum) and Bacillus cereus (B. cereus) are Gram-positive bacteria and the epitome of many serious opportunistic infections, including gas gangrene as well as wound, corneal, and gastro-intestinal infections. , As these bacteria resist the activity of many antibiotics (such as penicillin), they are still susceptible to the activity of gentamycin, vancomycin, erythromycin, and other antibiotics. , The pathogenicity of these microorganisms is linked to their secreted toxins and proteases, which assist them to elude defensive mechanisms, reach deep locations for nourishment, and consequently replicate and persist at the infection site . This might also enhance bacterial histotoxicity by promoting toxin diffusion .…”
Section: Introductionmentioning
confidence: 99%
“…In China, B . cereus is detected in a variety of foods [ 12 ], like dairy food [ 13 15 ], ready-to-eat products [ 16 ], and meat products [ 17 ]. The actual disease burden is underestimated due to a lack of holistic data on surveillance, posing a food safety risk globally.…”
Section: Introductionmentioning
confidence: 99%